KEMAMPUAN NETRALISASI KEKEBALAN TUBUH INDUK MELALUI KUNING TELUR AYAM PETELUR PADA VIRUS AI (H5N1) ISOLAT LAPANGAN - Haryanto, Agung Puji (Universitas Djuanda Bogor, 2020)
Day old chick in the first week of their life got the immunity from maternal antibody / immunoglobulin trough egg yolk. Hens with high antibody titer will decended the immunoglobulin to their harvest trough egg yolk. The research studied the capability of antibody anti H5N1 from egg yolk to neutralized H5N1 AIV. Twenty hens were devided to five group, one group as a control group were unvaccinated group and four other groups were vaccinated with H5N1 AI inactive vaccine produced by several Indonesia vaccine company. Four H5N1 AI inactive vaccines code VS1, VC1, VV1 and VM1 were vaccinated twice to group 2, 3, 4 and 5. A week after second vaccination the egg were collected and analyzed the antibody titer against H5N1 AIV by hemagglutination test using H5N1 AIV field isolates as standard virus (NG and LW)). The egg yolk were contain high antibody titer (above 26) collected and tested against H5N1 AIV field isolates NG and LW by serum neutralization test. The result showed that H5N1 AIV NG isolate were able to neutralized by antibody anti H5N1 AIV from egg yolk produced by hens vaccinated with VS1, VC1, VV1 and VM1, but LW isolate were able to neutralized by showed that H5N1 AIV NG isolate were able to neutralized by antibody anti H5N1 AIV from egg yolk produced by hens vaccinated with VS1, VC1, and VM1. It’s concluded that hens were vaccinated with H5N1 AI inactive vaccine were able to protect their off spring against H5N1 AIV from the field by transferred maternal antibody trough the egg yolk with titer above 26.